Ludai particles as a fillers in polypropylene thermoplastic composite / Juliya Mohamed @ Mohd Jusoh - Mohamed @ Mohd Jusoh, Juliya (2002)
This is a study of producing thermoplastic composite from sawdust of Ludai (sapium bacatum). Thermoplastic composite from Ludai is followed from 10%,30%, and 50%. Test such as bending, tensile, thickness, swelling and water absorption are carried out. The result showed that, 10% of sawdust of Ludai is very strength compare to 30% and 50%. The high content of PP to influences the results, as it will produce a perfect bounded between sawdust and PP. The thickness swelling and water absorption showed that the water could absorb into 50% than 30% and 10%. This is because wood are hydroscopic and more wood make it absorb more water. Generally, this composite produce can be use as a starting material for non-structural proposes.